Adaptation of New Rice High Yielding Varieties on New Constructed Irrigated Rice Field Affected by Sea Water Intrusion in West Tanjung Jabung District, Jambi - Saidi, Busyra Buyung; Hendri, Jon; Suharyon, Suharyon; Purnama, Hendri (UNIVERSITY OF LAMPUNG, 2020)
Assessment adaptation of several new superior rice varietiesÂ on new rice fields affected by seawater intrusion was carried out in Tungkal Ilir Subdistrict, West Tanjung Jabung District, from April to October 2018. The study applied randomized block designs (RBD) with four replications. The treatments consisted of four new rice high yielding varities suitable for tidal/swamps areas namely Inpara 3, Inpara 8, Inpara 9, and Inpari 34 Salin Agritan, and one local rice variety (Londo) as control. Three stems seedlings per clump were planted at the age of 21-25 days, using a 4:1 Legowo planting system. Fertilizer application consisted of basic fertilizer (1.0 Mg ha-1 of lime, 2.5 Mg ha-1 of manure, and 75 kg ha-1 of urea) and supplementary fertilizer (SP-36 150 kg ha-1 and KCl 125 kg ha-1),. Urea supplementation is given based on observations with a leaf color chart (LCC). The results of the study showed that the four new rice HYVs were more adapted as compared to the local rice variety. The performance of the tested new rice HYVs showed quite a good growth appearance and productivity. The highest production was obtained in Inpari 34 Salin Agritan variety 2.85 Mg ha-1, while Inpara 3, Inpara 8, and Inpara 9 ranged between 2.0 and 2.1 Mg ha-1, while the local varietyâ€™s productivity was 1.9 Mg ha-1.